Standardization of propagation methods in minor wild fruit crops (Current Horticulture, 2024)
The study was carried out to find out the ideal propagation techniques of wild and minor fruit crops at ICAR IIHR, Bengalure, during 2016-19. Two year’s data revealed that fresh seeds of most of the species, viz. karonda (Carrisa carandas), wood apple ( Feronia limonia syn. Limonia acidissima), avocado (Persea americana), noni (Morinda  citrifolia), wild jamun (Syzygium cumini), Alangeum (Alangium salvifolium), carombola (Averhoa carambola), Canito (Chrysophyllum cainito), bael (Aegle marmelos), kokum (Garcinia indica ), yellow mangosteen (Garcinia xanthochymus)  and Malabar tamarind (Garcinia gummigutta) did not have dormancy and their germination was more than 60 per cent. Although the days taken for germination varied in these fruits. Some fruits, viz. mulberry (Moris alba) gave good response (80%) for multiplication through cuttings. Air-layering was found successful in Governor’s plum (Flacourtia indica), Karonda (Carrisa carandas), natal plum (Carrisa macrocarpa), Citrus hindsi, Surinam cherry (Eugenia  uniflora ) and West Indian cherry ( Malpighia emarginata ) with 75 % and 60 % survival. The grafting was found successful (90%) in avocado (Persea americana) and wood apple (Feronia limonia ).
Keywords: Propagation; Standardization; Underutilized fruits; Wild fruits; Grafting